Palladium(II)-Catalyzed C(sp3)–H Activation of N,O-Ketals towards a Method for the β-Functionalization of Ketones - Ho, Danny K. H.; Calleja, Jonas; Gaunt, Matthew J. (Synlett, 2019)
A method for the formal β-functionalization of aliphatic ketones via a palladium-catalyzed sp3 C–H activation pathway is reported. An N,O-ketal directs an aliphatic C–H carbonylation to form γ-lactams which upon hydrolysis generate γ-keto carboxylic acids. This C–C bond-forming reaction is tolerant of a range of functional groups, enabling the synthesis of a range of synthetically important building blocks. Furthermore, the concepts underlying this transformation have also enabled the development of a related C–H alkenylation process to highly functionalised heterocycles.
Keywords: oxazolidine; palladium; carbonylation; lactam; ketone; C–H activation